Conflict Mitigation in Papua through a Criminal Policy Approach with the Aim of Social Welfare - Agus Tutupahar; Eriyantouw Wahid; Gunawan Djajaputra (International Journal of Social Service and Research, 2023)
Papua, which is located in the easternmost region of the archipelago, was included in the Unitary State of the Republic of Indonesia on November 19, 1969 through UN Resolution no. 2504. This is also at the same time the basis for recognition of Papua's integration with the Unitary State of the Republic of Indonesia according to international law. The handling and handling of the Papuan conflict is treated in various ways, including through a criminal policy approach, where criminal policy itself is a criminal policy, namely a concept of the existence of community protection to achieve community welfare. Thus, it can be said that criminal politics is also an integral part of social politics. Now what then becomes a number of problems is how the rationale and principles that form the basis for Indonesia as a rule of law make Criminal Policy as one of the approaches that can resolve conflicts in Papua in the Supremacy of Law, which in general provide guarantees for human rights, what is the history of the Papua conflict and its impact on Indonesia, what is the right model for tackling the Papua conflict through a criminal policy approach (Criminal Policy) within the Indonesian rule of law, in an effort to improve the welfare of society (Social Welfare). Research on the problems above was carried out using qualitative methods. The type of research used is normative (normative legal research) by using an approach with legal interpretation methods, with the object of study being an inventory of laws and regulations related to Papua conflict management through a criminal policy approach and applicable positive laws related to law enforcement. on Conflict Management by promoting the concept of Social Welfare. Based on the results of the research on the problems above, the handling of the conflict in Papua, the Government of Indonesia continues to prioritize the concept of criminal policy or Social Welfare, this has been proven, until now those who carry out agitation are still considered as armed criminal groups and not referred to as as separatist movements and terrorists. That apart from that, there are a number of things that need to be considered where the Papua conflict is a complex matter and requires an efficient and wise resolution, and the need to improve public understanding to increase the level of quality human resources in order to prevent conflicts from occurring.